2019
DOI: 10.1108/jm2-11-2018-0195
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic supply chain resilience model for medical equipment’s industry

Abstract: Purpose Medical equipment’s supply chains play a vital role in performance of national 1healthcare systems. This supply chain is confronted with different internal and external risks. The purpose of this study is to investigate and find the key factors affecting the resilience of the supply chain of medical equipment and to examine the dynamic relations among these factors. Design/methodology/approach A hybrid methodology is used for meeting the purpose of this study. First, the Delphi method is extended by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…Looking at the factors that constitute SCRES, Tukamuhabwa et al (2015) and Hohenstein et al (2015) determine that flexibility , redundancy , collaboration, and visibility are the most prominent antecedents. Senna et al (2020) and Jafarnejad et al (2019) confirmed these SCRES antecedents' importance in the healthcare context. Various procurement practices can enable these critical SCRES antecedents in a HCSC.…”
Section: Theoretical Backgroundsupporting
confidence: 52%
See 2 more Smart Citations
“…Looking at the factors that constitute SCRES, Tukamuhabwa et al (2015) and Hohenstein et al (2015) determine that flexibility , redundancy , collaboration, and visibility are the most prominent antecedents. Senna et al (2020) and Jafarnejad et al (2019) confirmed these SCRES antecedents' importance in the healthcare context. Various procurement practices can enable these critical SCRES antecedents in a HCSC.…”
Section: Theoretical Backgroundsupporting
confidence: 52%
“…Within our sample, we differentiated between two tiers of a HCSC – manufacturers and hospital groups. By individually investigating the respective tiers, we highlighted the importance of medical equipment and pharmaceutical suppliers for the overall performance of the HCSC ( Jafarnejad et al, 2019 ). Furthermore, the two-tier sample design enabled investigation of SCRES measures within and across tiers and in-depth exploration of BSRs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…climate change mitigation) that help to preserve ecosystems and prevent disasters related to environmental factors. On the other hand, studies on distributed dynamic supply management have proven how a distributed model enables a greater resilience of the whole system ( Mussomeli et al, 2016 ; Jafarnejad, Momeni, Razavi Hajiagha, & Faridi Khorshidi, 2019 ), providing holistic decision-making and rapid, no-latency responses to what may disrupt the supply chain, as occurred during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of BT on SC resilience (Petitt et al , 2019) depends on the technology's ability to provide visibility and make processes more flexible and agile (Jafarnejad et al , 2019), as well as to generate the adaptive capacity to react and restore operations, which may even avoid the need for redundancies (Brusset and Teller, 2017) and the propagation of events identified as a source of risk (Adobor, 2019; Kumar and Anabanandam, 2019). An example of this would be in the balance and control of inventory in the SC (Helo and Shamsuzzoba, 2020), given that BT aims to anticipate problems and create solutions accordingly, consequently allowing companies to act before the problem happens (Ali and Golgeci, 2019).…”
Section: Research Agenda and Discussionmentioning
confidence: 99%